1989
DOI: 10.1111/j.1476-5381.1989.tb16860.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by neuropeptides of interleukin‐1β‐induced, prostaglandin‐independent hyperalgesia

Abstract: The cytokine interleukin-lf (IL-I0) is a potent hyperalgesic agent in the rat whereas IL-la is relatively inactive (Ferreira et al., 1988). IL-1fi induced a dose-dependent increase in the sensitivity of rat paws to mechanical stimulation following intra-plantar injection but this effect was not reduced by indomethacin (1.Omgkg-1, p.o.), at a dose known to inhibit completely prostaglandin synthesis in the rat (Salmon et al., 1983). Prostaglandin (PG)E2 enhanced sensitivity to both mechanical pressure and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 10 publications
1
31
0
3
Order By: Relevance
“…Interestingly, this set of data is in agreement with previous work in which ␣-MSH was shown to inhibit IL-1␣-induced migration of neutrophils into subcutaneous sponges (Mason and Van Epps, 1989) whereas the effect observed with MS05 is novel. It is of interest that the ability of KPV to antagonize the effects of IL-1␤ has also been reported in IL-1-induced anorexia (Uehara et al, 1992) and hyperalgesia (Follenfant et al, 1989). The lack of effect of HFRW on IL-1␤ experiments confirms the lack of MC-R activation and would suggest that peptides that do not contain KPV exert their anti-inflammatory effect by inhibiting the release of chemokines and cytokines rather than their action.…”
Section: Dissection Of the Anti-inflammatory Effects Of Kpv 635supporting
confidence: 56%
“…Interestingly, this set of data is in agreement with previous work in which ␣-MSH was shown to inhibit IL-1␣-induced migration of neutrophils into subcutaneous sponges (Mason and Van Epps, 1989) whereas the effect observed with MS05 is novel. It is of interest that the ability of KPV to antagonize the effects of IL-1␤ has also been reported in IL-1-induced anorexia (Uehara et al, 1992) and hyperalgesia (Follenfant et al, 1989). The lack of effect of HFRW on IL-1␤ experiments confirms the lack of MC-R activation and would suggest that peptides that do not contain KPV exert their anti-inflammatory effect by inhibiting the release of chemokines and cytokines rather than their action.…”
Section: Dissection Of the Anti-inflammatory Effects Of Kpv 635supporting
confidence: 56%
“…In mice, intraplantar injection of PGE 2 into the hindpaw increased the response evoked by noxious heat stimulation as measured with the hot plate test (202). PGE 2 also reduced paw withdrawal latency to radiant heat stimulation, and this response was slightly reduced in mice with a targeted mutation of the type I regulatory subunit of PKA (463,787).…”
Section: Prostanoid-induced Sensitization To Heat Stimulimentioning
confidence: 94%
“…As studied by the modified Randall-Selitto test, PGE 2 or PGI 2 injected intraplantarly in the rat evoked mechanical hyperalgesia (193,202). The PGE 2 effect depended on activation of the cAMP-PKA pathway, and the PDE4 isoenzyme was shown to be involved in cAMP breakdown (124,194).…”
Section: Prostanoid-induced Sensitization To Mechanical Stimulimentioning
confidence: 99%
“…Several observations suggest a role for IL-1 in the peripheral modulation of nociception. In particular, it has been demonstrated that, when administered subcutaneously in the rat paw, IL-1 ␤ is able to produce a dose-dependent increase in the sensitivity to noxious stimulation (Ferreira et al, 1988;Follenfant et al, 1989;Cunha et al, 1991).…”
Section: Intra-plantar (I Pl) Injectionmentioning
confidence: 99%